Studies of mucus in mouse stomach, small intestine, and colon. II. Gastrointestinal mucus proteome reveals Muc2 and Muc5ac accompanied by a set of core proteins - Rodríguez-Piñeiro, Ana M. (American Physiological Society, 2013)
The mucus that protects the surface of the gastrointestinal tract is rich in specialized O-glycoproteins called mucins, but little is known about other mucus proteins or their variability along the gastrointestinal tract. To ensure that only mucus was analyzed, we combined collection from explant tissues mounted in perfusion chambers, liquid sample preparation, single-shot mass spectrometry, and specific bioinformatics tools, to characterize the proteome of the murine mucus from stomach to distal colon. With our approach, we identified ∼1,300 proteins in the mucus. We found no differences in the protein composition or abundance between sexes, but there were clear differences in mucus along the tract. Noticeably, mucus from duodenum showed similarities to the stomach, probably reflecting the normal distal transport. Qualitatively, there were, however, fewer differences than might had been anticipated, suggesting a relatively stable core proteome (∼80% of the total proteins identified). Quantitatively, we found significant differences (∼40% of the proteins) that could reflect mucus specialization throughout the gastrointestinal tract. Hierarchical clustering pinpointed a number of such proteins that correlated with Muc2 (e.g., Clca1, Zg16, Klk1). This study provides a deeper knowledge of the gastrointestinal mucus proteome that will be important in further understanding this poorly studied mucosal protection system.